2019
DOI: 10.1002/jbm.b.34383
|View full text |Cite
|
Sign up to set email alerts
|

Dual functional nanoparticles containing SOX duo and ANGPT4 shRNA for osteoarthritis treatment

Abstract: In our previous studies, we found that adult stem cells transfected with sex‐determining region Y‐box (SOX)‐9, ‐6 and ‐5 genes (SOX trio) enhanced chondrogenesis and suppressed the progression of osteoarthritis (OA). The inhibition of angiopoietin‐like 4 (ANGPT4) is known to reduce levels of cartilage damaging enzymes, such as, matrix metalloproteinases (MMPs). In this study, we designed nanoparticles comprising dexamethasone‐conjugated polyethylenimine (DEXPEI) complexed with minicircle plasmid (MC) harboring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The key to the treatment of OA is to expand phenotypic applicability, suppress inflammation and degrade joint tissues [7,8]. Although the current treatment methods for OA include mesenchymal stem cell therapy, nanoparticle therapy and infiltration therapy, the efficacy lacks effectiveness and applicability, so the pathogenesis of OA still needs to be clarified [9][10][11][12]. Therefore, it is of great significance for us to explore new targets to curb the progression of OA by understanding the molecular mechanism of OA.…”
Section: Introductionmentioning
confidence: 99%
“…The key to the treatment of OA is to expand phenotypic applicability, suppress inflammation and degrade joint tissues [7,8]. Although the current treatment methods for OA include mesenchymal stem cell therapy, nanoparticle therapy and infiltration therapy, the efficacy lacks effectiveness and applicability, so the pathogenesis of OA still needs to be clarified [9][10][11][12]. Therefore, it is of great significance for us to explore new targets to curb the progression of OA by understanding the molecular mechanism of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the use of differentiation signaling growth factors, some studies have induced differentiation through overexpression of SOX transcription factors in stem cells, which are known to be heavily involved in chondrogenesis. 126,127 Although SOX9 is known as the main chondrogenic transcription factor, in vivo delivery of cells has involved cells overexpressing both SOX9 and SOX6, as SOX6 enhances SOX9 activity. 128 One of the two studies, referenced in Table 5, uses ANGPTL4 shRNA along with SOX6 and SOX9 overexpression, as ANGPT4 has been shown to be higher in OA chondrocytes and induces MMP expression within them and stem cells.…”
Section: Gene-engineered Stem Cellsmentioning
confidence: 99%
“…128 One of the two studies, referenced in Table 5, uses ANGPTL4 shRNA along with SOX6 and SOX9 overexpression, as ANGPT4 has been shown to be higher in OA chondrocytes and induces MMP expression within them and stem cells. 127 Therefore, this approach may be more powerful as it is also counteracting negative genes associated with OA.…”
Section: Gene-engineered Stem Cellsmentioning
confidence: 99%
“…ASCs transfected with Sox gene‐harboring nanoparticles significantly enhanced chondrogenesis, showing higher expressions of the collagen type II gene and protein and suppression of matrix metalloproteinase 3 and 13 genes compared with control plasmid‐harboring nanoparticles. In vivo experiments using surgically induced OA in rats showed that Sox gene‐harboring nanoparticle transfected ASCs arrested the progression of OA in that model …”
Section: Gene‐enhanced Cartilage Regenerationmentioning
confidence: 99%
“…In vivo experiments using surgically induced OA in rats showed that Sox gene-harboring nanoparticle transfected ASCs arrested the progression of OA in that model. 56 As a preclinical study to test the feasibility of Sox gene-based gene cell therapy to treat OA, the authors have developed Sox-6, 9-transfected human adipose stem cells ( SOX-6, 9 ASCs). These were tested for their effectiveness in arresting OA progression when IA injected in a surgically induced OA caprine model.…”
Section: Overexpression Of Transcription Factors (Tfs) For Cartilage mentioning
confidence: 99%